2014
DOI: 10.5195/ijms.2014.97
|View full text |Cite
|
Sign up to set email alerts
|

Medical Students’ Knowledge and Attitudes Toward Female Sex Workers and Their Occupational Risk Factors

Abstract: Background: The tendency for female sex workers to seek health care is highly influenced by physician attitudes and behavior. By identifying medical students' attitudes toward female sex workers and assessing their knowledge of barriers to seeking care, we can focus medical training and advocacy efforts to increase access to care and improve public health outcomes. Methods: In this cross-sectional study, medical students from various countries were invited to participate in an online survey with close-ended qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…To the Editor, The article by Nakagawa and Akpinar-Elci on medical students' knowledge and attitudes toward female sex workers and their occupational risk factors left us with ambiguous reflections. 1 The crux of this study raises an important issue: sex work, sexual abuse toward women, and sexually transmitted diseases (STDs) are big problems and should be widely discussed in the medical environment. It is essential to provide care to female sex workers through educating medical students and young doctors, regardless of their religious and upbringing influences.…”
Section: Response To Medical Students' Attitudes Towards Female Sex Wmentioning
confidence: 99%
“…To the Editor, The article by Nakagawa and Akpinar-Elci on medical students' knowledge and attitudes toward female sex workers and their occupational risk factors left us with ambiguous reflections. 1 The crux of this study raises an important issue: sex work, sexual abuse toward women, and sexually transmitted diseases (STDs) are big problems and should be widely discussed in the medical environment. It is essential to provide care to female sex workers through educating medical students and young doctors, regardless of their religious and upbringing influences.…”
Section: Response To Medical Students' Attitudes Towards Female Sex Wmentioning
confidence: 99%
“…15 This stigma comes not only from the communities in which these women reside, but also from the health care providers who serve them. 6,[16][17][18][19] Such bias among health professionals highlights the importance of teaching health professions trainees about the social determinants of health in a way that is inclusive of sex workers; still, curricula addressing the social determinants of health remain inadequately researched. 20 Service learning has been presented as one strategy for teaching the social determinants of health and typically takes the form of health education initiatives targeting underserved populations.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted among 292 medical students of 56 countries through on-line surveys showed that religious minded respondents were significantly more likely to show negative attitude to provide treatment to FSWs compared to those who did not identify themselves as religious (82). Ashar etal raised many points in their study on service delivery mechanisms for FSWs which included single versus integrated interventions, optimum or minimum requirements for services, different type of service provision based on priority etc.…”
Section: Barriers In Service Deliverymentioning
confidence: 99%